MODERNIZATION AND THE ROLE OF PACKAGING IN INCREASING THE MARKETING OF GIPANG PRODUCTS IN MAWAR MICRO SMALL MEDIUM ENTERPRISES (UMKM) IN BANYUWANGI PULO AMPEL VILLAGE - Suflani Suflani; Mochamad Fahru Komarudin; Martinus Rambe Purba; Kemal Firdaus; Asarah Asarah; Yus Resya Adesta (Yayasan Education and Social Center, 2023)
Gipang is a typical Banten food, one of which is made by residents of Banyuwangi Village, Pulo Ampel District, Serang and Gipang Regencies. Digital technology is currently developing Gipang Rice and Cassava production based on orders. MSMEs are the backbone of the national economy. This sector is able to drive the community's economy and absorb a large number of workers. Unfortunately, the packaging for Gipang Rice and cassava products in Banyuwangi Village still uses non-standard jars and plastic, therefore packaging modernization is the solution. Standard packaging modernization can make gipang products durable and not easily destroyed and can attract the attention of buyers so that they can increase the marketing of Gipang Rice and Cassava products. By improving MSME packaging it is proven to be able to increase marketing, the market segment is increasing, and marketing turnover is increasing so that MSME can be upgraded